2003
DOI: 10.1136/ip.9.3.245
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime driving, passenger transport, and injury crash rates of young drivers

Abstract: Objective:This study examines the association of nighttime driving and the carrying of passengers with the rate of motor vehicle crashes that resulted in severe or fatal injury to young drivers in California before the implementation of a graduated licensing system.Method:Passenger vehicle drivers aged 16 or 17 involved in injury crashes in California from 1 January 1993 to 30 June 1998 were identified through a police crash database. An induced exposure method was used to estimate driving exposure. Odds ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(61 citation statements)
references
References 29 publications
5
54
1
1
Order By: Relevance
“…Indeed, survival from out‐of‐hospital cardiac arrests was reported to be poor during the night‐time and on holidays in Japan 12. In addition, traffic accidents occurring during holidays and weekends and at night are frequently associated with alcohol, drugs, and drowsy driving, and tend to involve severely injured victims, which may be related to the difficulty in finding hospitals to receive patients 13, 14, 15. Medical resource allocation is one of the important issues in an emergency medical system, and both medical institutions and local governments must arrange a system such that emergency patients can be transported and accepted without delay 24 h a day, 7 days a week.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, survival from out‐of‐hospital cardiac arrests was reported to be poor during the night‐time and on holidays in Japan 12. In addition, traffic accidents occurring during holidays and weekends and at night are frequently associated with alcohol, drugs, and drowsy driving, and tend to involve severely injured victims, which may be related to the difficulty in finding hospitals to receive patients 13, 14, 15. Medical resource allocation is one of the important issues in an emergency medical system, and both medical institutions and local governments must arrange a system such that emergency patients can be transported and accepted without delay 24 h a day, 7 days a week.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 The importance of supervisor age is underscored by data from Chen et al, 27 who found the highest case-fatality rates of 16-year-old drivers in crashes when passengers aged 20 to 29 years were present. This might be related to the fact that older passengers may legally buy alcohol and (illegally) provide it to underage drinkers, although Rice et al 28 indicated that the presence of adults aged 20 to 29 was associated with severe or fatal injury among 16-and 17-year-old drivers even when alcohol use was controlled for. Williams and Shabanova 29 reported that teen drivers were less likely to use seat belts when passengers were in their 20s, and recommended that passenger restrictions not be waived unless there is a supervisor Ն30 years of age.…”
Section: Limitationsmentioning
confidence: 93%
“…Both male and female young drivers experience this increased risk (Chen et al, 2000;Doherty, Andrey, & MacGregor, 1998). Although crash risk is elevated when teenage drivers carry sameage peers, adult passengers reduce the risk of a crash for young, beginning drivers (Aldridge et al, 1999;Ouimet et al, 2010;Rice, Peek-Asa, & Kraus, 2003). Passengers' sex also appears to be related to young drivers' crash risk.…”
Section: Discussionmentioning
confidence: 93%